UTILIZATION OF BROILER CHICKEN BYPRODUCT (ABDOMINAL FAT) AS A WOUND HEALING AGENT - Yunus, Muhammad; Beddu, Hartina; Hidayat, Nuzul (Buletin Veteriner Udayana, 2025)
Traditional medicine is of sufficient concern to continue to be developed and strive to become part of formal medicine in Indonesia, in line with the "back to nature" trend. This study aims to evaluate the effectiveness of using broiler waste (abdominal fat) as a wound medicine. This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications, resulting in 12 samples. The treatment group was divided into 4 treatments, namely: Positive Control (P0), 1 time a day (P1), 2 times a day (P2), 3 times a day. The parameters observed were calculation of wound length, wound healing time, wound drying. Extension evaluation is an initial evaluation and final evaluation with a questionnaire. The results of the study showed that the fastest wound closure was P1, P2, P3 on day 14, while P0 wound closure had not occurred on day 14. This shows that chicken tallow oil P1, P2, P3 has faster wound closure activity when compared with betadine as a positive control. For further information, it is recommended to test the bacterial inhibitory parameters and identify the compounds present in the chicken fat oil.